Investigating Reinforced Concrete Beams with Web Opening under Static and Cyclic Loads - Ali Fawzy; Arafa EL-Helloty; Mahmoud Hassan Mahmoud; Aymen Summra (Journal of Engineering)
This study aims to investigate experimentally and theoretically the behavior of reinforced concrete beams with openings subjected to static and cyclic loads. The experimental program consists of testing eight specimens with a rectangular opening at the shear zone, two of the beams serve as a control beam (without openings) subjected to static and cyclic loads, three beams with rectangular openings of variable height and subjected to static loads, and three beams with rectangular openings of variable height and subjected to cyclic loads. All openings were rectangular of constant length and varied at heights of 20%, 30%, and 40% of the beam height. The beams were loaded at two points using a steel plate until the failure stage was reached. Numerical studies were performed on ANSYS software, and the finite element results were verified through experiments. The response has been discussed in terms of the deformation occurring in all beams, the crack pattern, and failure modes, resulting from static and repeated loading. Results indicated that the load failure of the beams subjected to cyclic loads decreased by a rate ranging from 86% to 90% of those static loads. The results also showed that the load failure rate decreases as the opening height increases. The percentages of decrease were (58%, 62%, and 90%) compared to the load failure rate of the control beam (without opening), which corresponds to opening heights of 20%, 30%, and 40% of the beam’s height.